Correlated Measurement Errors, Bounds on Parameters, and a Model of Producer Behavior - Yngve Willassen; Tor Jakob Klette (Statistics Norway, Research Department, 1994)
We examine estimation of a model of producer behavior in the presence of correlated measurement errors in the regressors. Scale economies and price-cost margins are estimated from a set of panel data for manufacturing plants. The paper presents a somewhat new model for estimation of these parameters which is highly flexible but with a simple regression structure. Perhaps the most important contribution of the paper is some new results on deriving parameter bounds for a regression model with errors in variables. In particular, we consider the case where the measurement errors might be correlated. We derive asymptotic standard errors for the parameter bounds. These asymptotic standard errors are compared to bootstrap estimates. Our new results on parameter bounds are applied to the estimation of the model of producer behavior.
Keywords: C13; C29; C43; 330; Estimation; errors-in-variables; parameter bounds; imperfect competition; scale economies.